2020
DOI: 10.1149/2162-8777/ab8b4d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cr3+ and Mg2+ Impurities on Thermoluminescence and Deep Traps in β-Ga2O3 Crystals

Abstract: Thermally stimulated luminescence (TSL) of β-Ga2O3 single crystals doped with Cr3+ and Mg2+ impurities was investigated. Based on the correlation between the Cr3+ concentration and light sum accumulated in the thermoluminescence (TL) glow peak at 285 K, it was concluded that doping of β-Ga2O3 with Cr3+ ions leads to the formation of electron traps manifested in this peak. The activation energy of peak at 285 K is equal to Ec-0.55 eV and close to E1. Thus the Cr3+e− centers can be a candidate for E1. The high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
(76 reference statements)
2
24
0
2
Order By: Relevance
“…While the unambiguous assignment of these traps is notoriously difficult, some of these levels have been attributed to intentional or unintentional dopants, such as Fe, Cr and Mg or to intrinsic defects, such as O vacancies, or complex defects involving them. In particular, a defect complex involving Fe and intrinsic defects, with an energy level lying 0.7 eV below the conduction band minimum, was reported, and a correlation between its concentration and the Cr 3+ luminescence was observed 22 . Additionally, the charge transfer level Fe 2+ /Fe 3+ (energy level lying 0.78 eV below the conduction band minimum 29 ) was proposed to act as a charge transfer channel to Cr ions in the 4+ charge state 35 .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…While the unambiguous assignment of these traps is notoriously difficult, some of these levels have been attributed to intentional or unintentional dopants, such as Fe, Cr and Mg or to intrinsic defects, such as O vacancies, or complex defects involving them. In particular, a defect complex involving Fe and intrinsic defects, with an energy level lying 0.7 eV below the conduction band minimum, was reported, and a correlation between its concentration and the Cr 3+ luminescence was observed 22 . Additionally, the charge transfer level Fe 2+ /Fe 3+ (energy level lying 0.78 eV below the conduction band minimum 29 ) was proposed to act as a charge transfer channel to Cr ions in the 4+ charge state 35 .…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the optical activation of the Cr 3+ ions in β -Ga 2 O 3 , the excitation processes are not fully understood yet, due to the large number of possible defect states in this material that can be responsible for the sensitization. Such processes include energy or charge transfer between traps in β -Ga 2 O 3 and Cr 3+ ions 22 25 . Recent IBIL measurements monitored at the Cr 3+ emission wavelengths show a strong enhancement of the emission intensity as a function of the irradiation fluence in a conductive sample, thus suggesting that irradiation-induced defects play a major role in the activation of this luminescence 23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the internal transitions between the 2 E and 4 A 2 states of Cr 3þ give rise to two sharp emission (or absorption) lines at around 1.78 and 1.80 eV at room temperature (RT), which were labeled as R1 and R2 lines. 18,19,[22][23][24][25][26][27][28][29][30] This conclusion was based 19,22,23,25 on a similarity of the transition energies with the internal transitions of Cr 3þ in Al 2 O 3 . [31][32][33] They were further supported by the analysis of higher-lying excited states detected in absorption 19,28 and emission 18,22,[24][25][26][27][28] spectra of Cr-doped b-Ga 2 O 3 , as well as photoluminescence excitation spectra of the R lines 24,26,28 using the Tanabe-Sugano diagrams.…”
mentioning
confidence: 99%